(untitled) (Journal of Science and Technology Research, 2026)
Rivers play a pivotal role in the hydrologic cycle, and in Dhaka, a bustling metropolitan city surrounded by four rivers/khals, rapid population growth has led to adverse effects on these water bodies. The unplanned urbanization for the growing population has caused excessive pollution and contamination, turning the rivers into lifeless swamps. Over time, the land area, water quantity, and quality have steadily decreased. This study aims to address this gap by utilizing multispectral satellite images with field validation to perform spatiotemporal assessments of seasonal water bodies extent and quality in the peripheral rivers of Dhaka city. One of the main objectives of the study is to rank the peripheral rivers with respect to trophic status indexing. The normalized differential water indices were used to retrieve the river water bodies of the study area. The conventional methods of trophic status index with suspended sediment concentration, chlorophyll a concentration and Secchi disk depth of lake water body were applied in this study. The study observed that the extent of water bodies was reduced by about 16% due to urbanization or transformation of the rivers into land between 1977 to 2023. Seasonal water quality parameters showed mostly eutrophic conditions with minor areas of hyper-eutrophic condition in Turag River. Considering the observed water quality parameters, the examined rivers are no longer suitable for any purposes such as drinking, fisheries or even agriculture. The geospatial techniques and field validation both indicated pollution in all the four water bodies. J. of Sci. and Tech. Res. 6(2): 77-96, 2025